Dexter. The fourth season [videorecording (DVD)] - Benz, Julie, 1972-; Hall, Michael C., 1971-; Remar, James; Vélez, Luna, 1964-; Lee, C. S. (Charlie S.), 1971-; Lindsay, Jeffry P. (Paramount Pictures, 2010)
America's favorite serial killer has gone from freewheeling bachelor to responsible husband and doting dad. Maintaining an average-guy facade while satisfying his need to kill has never been easy. But now, with wife and kids in tow, Dexter's got more to lose than ever, as he gets drawn into a deadly game with a killer every bit as dangerous and conflicted as he is.